Analysis on the problems faced by contractors implementing traditional and design & build contract in Malaysia - Norziatul Husna, Mohd Ridzuan (2012)
Traditional contract and Design & Build contract has been part of the construction industry. Nowadays, the process is growing rapidly in this industry. As it has been grown in popularity, Traditional contract and Design & Build has evolved all manner of hybrids. However, Traditional contract and Design & Build also not exclude were faced problem by contractors in the construction industry such as conflicts between contractor and other parties (consultant and owner), inadequate experience of consultant, problems communication and coordination by contractor with other parties. The aims of the study are to analyze the comparisons of the project characteristics between Traditional contract and Design & Build contract and to analyze the common problems and the factors lead to the problems faced using both of the methods. The questionnaires were distributed to the contractor's Bumiputera companies (Class A, B, C and D) registered with Pusat Khidmat Kontraktor (P1(K) and Construction Industry Development Board (CIDB). The area of study cover Selangor and Kuala Lumpur for the west coast, Pahang for the east coast, Penang for the northern, and Johor for the southern of Malaysia. The data from the questionnaire was analyzes in average index and frequency analysis. The average index for the five categories of problems was identified. There are problems in general aspect, problems in design aspect, problems in financial aspect, problems in quality aspect and problems in time aspect. From the analysis, Design & Build is the most effective procurement contract for project delivery in Malaysia construction industry. The reason for implementing better contract procurement is to reduce the cost and speeding up the process of construction project.